Use of Pomegranate Peel Powder as an Alternative to Artificial Antioxidant in Chicken Meatballs - Shrestha, Kanti; Dhungel, Abhitosh; Dahal, Sagar (Tribhuvan University Journal of Food Science and Technology, 2024)
Pomegranate peel powder (PPP) is a potential source of antioxidants because of its higher content of polyphenols and ascorbic acid. The objective of the study is to prepare the PPP, investigate the physico-chemical properties and its effects as a natural antioxidant on the chicken meatballs. Meat samples with added PPP, reference antioxidant TBHQ, and the blank sample was run without any additives. Fat oxidation by peroxide value, pH, Sensory and functional properties of meatballs were compared. High fat content in meat is a major cause of oxidative deterioration, which can be resolved by the addition of antioxidant-rich sources like pomegranate peel. The study revealed that the PPP possesses average values of moisture content, crude fiber, crude fat, total ash, acid-insoluble ash (AIA), and L-ascorbic acid within the range of 7.998±0.238%, 10.362±1.608%, 1.0195±0.145%, 5.589±0.251%, 0.516±0.026%, 92.5±1.05mg/kg, respectively. Increasing peroxide value (PV) with time was reduced on adding PPP, which was in the order of Free sample > 1% PPP > 3% PPP > 6% PPP > 100 ppm TBHQ. On the 6th day, 100 ppm TBHQ and 6% PPP show no significant difference in peroxide value (9.271±0.04, 9.604±0.11 mEq/Kg, respectively) and are below the limit (10 mEq/Kg), which suggests that TBHQ can be replaced with 6% PPP in meatballs as a natural antioxidant. The study revealed that adding PPP will improve the oxidative stability and cooking quality of chicken meatballs by reducing fat oxidation.